Effects of the combined use of glutamine and growth hormone in the intestinal adaptation after massive resection of the small bowel in rats - Spadoni,Joaquim M. (2005)
PURPOSE: The aim of this study was to investigate the effects of the combined use of glutamine (GL) and growth hormone (GH) in the intestine of rats submitted to 80% small bowel resection. METHODS: [24] Twenty four Wistar rats were randomized to receive either a standard rat chow - control group (CG, n=12) or the same diet added to 4% glutamine - GL-GH group (n=12) after 80% enterectomy. The latter group received subcutaneously 0,6UI/day of GH. Groups of six rats in each group were killed on the 5th and 14th days. The following variables were studied: body weight, mucosal weight, histomorphometry and DNA content in the resected specimen and in the adapted intestines after necropsy. RESULTS: All animals lost weight stabilizing after the 5th PO day in both groups. There was not any statistical difference in the mucosal weight associated to groups and dates. However, ileal mucosal weight decreased from basal to final results when compared to jejunal mucosa (p= 0.02). The DNA content increased from the initial to the final results (p <0.001) in both groups, though, this increase was greater in GL-GH animals (CG = 0.53 [95% CI, 0.44-0.62] g/cm-1 vs. GL-GH= 0.85 [95%CI, 0.76-0.94] g/cm-1; p<0.01), especially at the 14th day. Ileal DNA content was significantly greater than jejunal (p=0.01). There was a significant increase in the intestinal wall width and crypt depth in the control group (p<0.01). CONCLUSION: Gut adaptation after massive resection is improved with the combined use of glutamine and GH.